2021
DOI: 10.3390/rs13234887
|View full text |Cite
|
Sign up to set email alerts
|

Coordination Conflicts between Urban Resilience and Urban Land Evolution in Chinese Hilly City of Mianyang

Abstract: Urban resilience, the combinational characteristic of nature and society, that reflects the dynamic accumulation process that is multi-level and multi-dimensional. Particularly, the rational spatial distribution structure of land mixture and compactness is an effective way to improve urban resilience because the evolution of morphology and density of the urban land blocks in the process of land spatial conversion reflect the performance characteristics of complexity, diversity, stability, compactness, and conn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…The building dynamics of Moncongloe-Pattalassang new city area tends to be directed towards rural development on a dominant large scale, meaning its occurrence is only oriented to support housing necessities for the new arrival based on income and economic levels. However, location, distance, revenue, population density, congestion, and education significantly explain the formation of housing types and other important factors, with minor convergence between separate, semi-detached, and multilevel designs [37]. The fact in the field showed that the ability of different owners of the residence facilities and the economic and social activity pattern affect the distinction of infrastructural service characteristics and the fulfillment of rural facilities.…”
Section: A Socio-economic Characteristics Of New City Regionmentioning
confidence: 99%
“…The building dynamics of Moncongloe-Pattalassang new city area tends to be directed towards rural development on a dominant large scale, meaning its occurrence is only oriented to support housing necessities for the new arrival based on income and economic levels. However, location, distance, revenue, population density, congestion, and education significantly explain the formation of housing types and other important factors, with minor convergence between separate, semi-detached, and multilevel designs [37]. The fact in the field showed that the ability of different owners of the residence facilities and the economic and social activity pattern affect the distinction of infrastructural service characteristics and the fulfillment of rural facilities.…”
Section: A Socio-economic Characteristics Of New City Regionmentioning
confidence: 99%
“…Changes in land use significantly affect the value of ecosystem services (ESV), ecosystem functions and urban resilience reflecting a multi-level and multi-dimensional dynamic accumulation process [37,38]. Thus, government policy support is needed to anticipate environmental damage and the risk of flood threats through disaster mitigation of the impacts [39,40].…”
Section: Determinants Of Land Use Change In the New City Areamentioning
confidence: 99%
“…As a complex system integrating social, economic, ecological, and infrastructural aspects [4], cities are inevitably impacted by various risks such as natural disasters, climate change, and public emergencies [5]. As an important strategy to reduce urban risk, urban resilience has received increasing attention [6][7][8].…”
Section: Introductionmentioning
confidence: 99%